All-Pass Filter Based Linear Voltage Controlled Quadrature Oscillator. (29th August 2017) - Mathur, Koushick; Venkateswaran, Palaniandavar; Nandi, Rabindranath
Abstract : A linear voltage controlled quadrature oscillator implemented from a first-order electronically tunable all-pass filter (ETAF) is presented. The active element is commercially available current feedback amplifier (AD844) in conjunction with the relatively new Multiplication Mode Current Conveyor (MMCC) device. Electronic tunability is obtained by the control node voltage (V ) of the MMCC. Effects of the device nonidealities, namely, the parasitic capacitors and the roll-off poles of the port-transfer ratios of the device, are shown to be negligible, even though the usable high-frequency ranges are constrained by these imperfections. Subsequently the filter is looped with an electronically tunable integrator (ETI) to implement the quadrature oscillator (QO). Experimental responses on the voltage tunable phase of the filter and the linear-tuning law of the quadrature oscillator up to 9.9 MHz at low THD are verified by simulation and hardware tests.